Emerging nanomedicine strategies for hepatocellular carcinoma therapy - Chen Guo; Jiayu Zhang; Xiaomeng Cai; Rui Dou; Jiaruo Tang; Zhengyuan Huang; Xueting Wang; Yan Guo; Hanqing Chen; Jun Chen (iMetaOmics)
Abstract Hepatocellular carcinoma (HCC) is a prevalent malignant tumor with a range of risk factors, including viral infections, alcoholic liver disease, exposure to fungal toxins, obesity, and type 2 diabetes. Despite advancements in early detection and treatment, HCC continues to exhibit a high rate of recurrence. Patients in advanced stages have a poor prognosis, and the survival rate after cancer metastasis is notably low. Consequently, there exists an urgent necessity for novel treatment strategies. Nanomedicine possesses superior attributes, such as targeted administration and responsive drug release within the tumor microenvironment. These systems demonstrate potential in HCC treatment by facilitating the transportation of diverse therapeutic drugs. This comprehensive review aims to delve into the application of nanoparticle drug delivery systems in the management of liver tumors, with particular emphasis on formulation, targeted strategies specific to liver tumors, and various methods of drug release. By offering insights into the utilization of nanoparticle drug delivery systems in the realm of liver tumor treatment, this review endeavors to assist readers in exploring their vast potential.